2012
DOI: 10.2174/156720512799015109
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Hormone-Based Therapeutics for the Treatment of Alzheimers Disease

Abstract: In both men and women, age-related loss of sex steroid hormones has been linked to an increased risk for Alzheimer's disease (AD). The primary female hormone estrogen, and the primary male hormone testosterone have numerous protective effects in the brain relevant to the prevention of AD such as the promotion of neuron viability, reduction of β- amyloid accumulation and alleviation of tau hyperphosphorylation. Therefore it has been hypothesized that the precipitous loss of these hormones either through menopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 219 publications
(312 reference statements)
1
29
0
2
Order By: Relevance
“…The primary female hormone estrogen and the 504 primary male hormone testosterone have numerous protective 505 effects in the brain relevant to the prevention of AD such as the 506 promotion of neuron viability, reduction of Ab accumulation and 507 alleviation of tau hyperphosphorylation. Complications are asso-508 ciated with estrogen-based hormone therapy such as the inclusion 509 of a progestrogen, hormone responsiveness with age, and natural 510 vs. synthetic hormones [100].…”
mentioning
confidence: 99%
“…The primary female hormone estrogen and the 504 primary male hormone testosterone have numerous protective 505 effects in the brain relevant to the prevention of AD such as the 506 promotion of neuron viability, reduction of Ab accumulation and 507 alleviation of tau hyperphosphorylation. Complications are asso-508 ciated with estrogen-based hormone therapy such as the inclusion 509 of a progestrogen, hormone responsiveness with age, and natural 510 vs. synthetic hormones [100].…”
mentioning
confidence: 99%
“…8,9 Both mouse and human studies have implicated menopause-related hormone deficiencies in this elevated risk profile. 46,47 Specifically, menopause causes rapid and significant decline in estrogen and progesterone, which could contribute to AD pathology; 48 further, estrogen levels significantly impact adaptive immunity. 49 Indeed, the earliest decline of Aβ-specific CD4 + T cells occurred in women who carried ApoE4 , reaching 50% of maximal around the age of 50, within the perimenopausal period for most women.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of these changes that is most frequently considered is a rapid decline in sex hormones after menopause, and in consequence, the deterioration of cognitive functions. This theory has been confirmed by many studies, which showed the neuroprotective role of oestrogens and androgens on the nerve cells [12][13][14]. Nevertheless, investigations of the effect of oestrogen supplementation on cognitive functions after menopause did not bring about an unequivocal confirmation of this theory [15][16][17].…”
Section: Introductionmentioning
confidence: 92%